The Influence of Store Attribute on Customer Experience and Brand Loyalty - Ahmad Khabib Dwi Anggara; Ririn Tri Ratnasari (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Industri fashion muslim di Indonesia saat ini sedang mengalami transformasi besar yang didorong oleh beberapa tren. Seiring dengan adanya transformasi teknologi saat ini, media sosial sebagai tempat berekspresi diri mendorong munculnya fast fashion yang mengacu pada praktik industri di mana pelaku industri fashion menawarkan berbagai macam produk baru dengan konsep pergantian mode yang cepat dan paling disukai pasar. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh store attribute terhadap customer experience, dan brand loyalty pada toko Hijup. Pengumpulan data dilakukan dengan kuesioner yang melibatkan 150 responden yang pernah mengunjungi dan berbelanja di toko Hijup dalam 12 bulan terakhir. Metode Path Analysis dilakukan untuk mengetahui bagaimana store attributes mempengaruhi customer experience dan brand loyalty dalam industri ritel fashion. Hasil penelitian menunjukkan bahwa store attribute memiliki pengaruh positif signifikan terhadap customer experience di dalam toko Hijup. Kemudian, ditemukan juga pengaruh positif signifikan antara customer experience terhadap brand loyalty. Adanya penelitian ini diharapkan dapat membantu toko Hijup sebagai pelaku retail khususnya di industri fashion muslim untuk meningkatkan store attribute mereka sehingga para peretail dapat menciptakan loyalitas bagi konsumen mereka. Kata kunci:  Store Attribute, Customer Experience, Brand Loyalty, Toko Hijup. ABSTRACT The Muslim fashion industry in Indonesia is currently undergoing a major transformation shared by several trends. Along with the current technological transformation, social media as a place for self-expression encourages the emergence of fast fashion which refers to industrial practices where fashion industry players offer a variety of new products with the concept of rapid change and are most favored by the market. This study aims to determine how the influence of store attributes on customer experience, and brand loyalty at Hijup stores. Data were collected using questionnaires involving 150 respondents who had visited and purchased at Hijup stores in the last 12 months. The path Analysis method was conducted to find out how store attributes affect customer experience and brand loyalty in the fashion retail industry. The results showed that store attributes had a significant positive effect on customer experience in Hijup stores. Then, it was also found that there was a significant positive effect between customer experience on brand loyalty. This research is expected to help Hijup stores as retail players, especially in the Muslim fashion industry to increase their store attributes so that retailers can create loyalty for their consumers. Keywords: Store Attribute, Customer Experience, Brand Loyalty, Hijup Store.   DAFTAR PUSTAKA Bıçakcıoğlu, N., Ilayda, İ., & Bayraktaroğlu, G. (2016). Antecedents and outcomes of brand love: the mediating role of brand loyalty. Journal of Marketing Communications, 24(8), 1–15. https://doi.org/10.1080/13527266.2016.1244108 Bilgihan, A. (2016). Gen Y customer loyalty in online shopping: An integrated model of trust, user experience and branding. Computers in Human Behavior, 61, 103–113. https://doi.org/10.1016/j.chb.2016.03.014 BRP & Windstream E. (2018). Retail’s digital crossroads: The race to meet shopper expectations. Retrieved from https://www.windstreamenterprise.com/wp-content/uploads/2018/07/windstream-retail-pov.pdf Choi, T. (2013). Fast fashion systems: Theories and applications. Florida USA: CRC Press. Finn, A. (2004). A reassessment of the dimensionality of retail performance: a multivariate generalizability theory perspective. Journal of Retailing and Consumer Services, 11(4), 235-245.  http://dx.doi.org/10.1016/S0969-6989(03)00050-X Gentile, C., Spiller, N., & Noci, G. (2007). How to sustain the customer experience: an overview of experience components that co-create value with the customer. European Management Journal, 25(5), 395-410. https://doi.org/10.1016/j.emj.2007.08.005 Ghosh, P., Tripathi, V., & Kumar, A. (2010). Customer expectations of store attributes: A study of organized retail outlets in India. Journal of Retail & Leisure Property, 9(1), 75-87. Giddens. (2002). Customer loyalty: Menumbuhkan dan mempertahankan kesetiaan pelanggan. Jakarta: Erlangga. Hartman, K. B., & Spiro, R. L. (2005). Recapturing store image in customer-based store equity: a construct conceptualization. Journal of Business Research, 58(8), 1112-1120. https://doi.org/10.1016/j.jbusres.2004.01.008 Jackson, C. (2006). Driving brand loyalty on the web. DMI Review, 17(1), 62-67. https://doi.org/10.1111/j.1948-7169.2006.tb00031.x Khan, I., Hollebeek, L. D., Fatma, M., Islam, J. U., & Arkonsuo, L. R. (2020). Customer experience and commitment in retailing: Does customer age matter? Journal of Retailing and Consumer Services, 57. https://doi.org/10.1016/j.jretconser.2020.102219 Lemon, K. N., & Verhoef, P. V. (2016). Understanding customer experience throughout the customer journey. Journal of Marketing, 80(6), 69–96. https://doi.org/10.1509%2Fjm.15.0420 Lindquist, J. D. (1974). Meaning of image. Journal of Retailing, 50(4), 29-38. Mohd-Ramly, S., & Omar, N. A. (2017). Exploring the influence of store attributes on customer experience and customer engagement. International Journal of Retail & Distribution Management, 45(11), 1138–1158. https://doi.org/10.1108/IJRDM-04-2016-0049. Jain, R., Aagja, J., & Bagdare, S. (2017). Customer experience–a review and research agenda. Journal of Service Theory and Practice, 27(3), 642–662. https://doi.org/10.1108/JSTP-03-2015-0064. Nikhashemi, S. R., Tarofder, A. K., Gaur, S. S., & Haque, A. (2016). The Effect of customers’ perceived value of retail store on relationship between store attribute and customer brand loyalty: Some insights from Malaysia. Procedia Economics and Finance, 37, 432–438. https://doi.org/10.1016/S2212-5671(16)30148-4 Machtiger, Kate. (2020). What will the retail experience of the future look like?. Harvard Business Review. Retrieved from https://hbr.org/2020/06/what-will-the-retail-experience-of-the-future-look-like Shaw, C., & Ivens, J. (2007). Building great customer experience. New York: Palgrave, Macmillan The Jakarta Post. (2020). Indonesia's e-commerce sales to surpass India's.  Retrieved from https://www.thejakartapost.com/news/2020/09/08/indonesias-e-commerce-sales-to-surpass-indias.html Verhoef, P. C., Lemon, K. N., Parasuraman, A., Roggeven, A., Tsiros, M., & Schlesinger, L. A. (2009). Customer experience creation: Determinants, dynamics and management strategies. Journal of Retailing, 85(1), 31–41. https://doi.org/10.1016/j.jretai.2008.11.001. Wang, C. H., & Ha, S. (2011). Store attributes influencing relationship marketing: A study of department stores. Journal of Fashion Marketing and Management: An International Journal, 15(3), 326–344. doi:10.1108/13612021111151923 Williams, L., Buoye, A., Keiningham, T. L., Aksoy, L. (2020). The practitioners’  path to customer loyalty: Memorable experiences or frictionless experiences? Journal of Retailing Consumer Service, 57. https://doi.org/10.1016/j.jretconser.2020.102215